2011
DOI: 10.1590/s1983-14472011000200019
|View full text |Cite
|
Sign up to set email alerts
|

Resolutividade da assistência e satisfação de usuários da Estratégia Saúde da Família

Abstract: The following research is a quantitative-qualitative study that aimed to analyze the view of users on the problem-solving capacity of care in a Family Health Unit and its relation with their satisfaction. The quantitative data were collected through a semi-structured form. The results showed the fact that 61.3% of users had their problems solved always or most times. The view of users on the problem-solving capacity is related to how they perceive their health problems' solution, and, for some, is associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
33

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 12 publications
0
18
0
33
Order By: Relevance
“…Thus, we see the importance of this exchange among professionals so that the proposal of the clinic is enabled and it is also worth highlighting the bonds that are created between the user-service, resulting in incentive for staff to provide quality of care and seek a positive partnership (26) . We can say that the discourses of participants reinforce something that was proposed in the study of Rosa, Pelegrini and Lima (22) , who claim the need to reorganize the process of working through community involvement in the planning of actions in order to trace interventions more assertive, and corresponding to the needs and expectations of it. Such capabilities are associated with the proposal of the clinic is to be a model in health care and community participation.…”
Section: Practice In the Service Related To The Expanded Clinicmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, we see the importance of this exchange among professionals so that the proposal of the clinic is enabled and it is also worth highlighting the bonds that are created between the user-service, resulting in incentive for staff to provide quality of care and seek a positive partnership (26) . We can say that the discourses of participants reinforce something that was proposed in the study of Rosa, Pelegrini and Lima (22) , who claim the need to reorganize the process of working through community involvement in the planning of actions in order to trace interventions more assertive, and corresponding to the needs and expectations of it. Such capabilities are associated with the proposal of the clinic is to be a model in health care and community participation.…”
Section: Practice In the Service Related To The Expanded Clinicmentioning
confidence: 64%
“…According to the study, 2012 (20) , the expanded clinic comes as a facilitator for comprehensive care, requiring a rethinking of the technical organization of work, thus, enabling proper support to establish a bond with the community attended. And that access for that user at the facility, should be determined by resoluteness of the actions provided to the type of user health problem (21)(22)(23) .…”
Section: Practice In the Service Related To The Expanded Clinicmentioning
confidence: 99%
“…This fact extrapolates the narrow idea of effectiveness based on the cure of diseases, but it also considers effectiveness with respect to relief of symptoms and minimization of suffering, as well as the promotion and maintenance of health (25) . Concerning the Neonatal Auditory Screening (NAS), the teams are knowledgeable about the test as a way to detect possible auditory changes, but they claim lack of access to it.…”
Section: Discussionmentioning
confidence: 92%
“…This can be justified by the fact that the resolution is related to the user's perception about the solution of their health problem by specialized care (25) . As there are difficulties in conducting the referrals and delay in scheduling the consultations -which compromise the integrality of the assistance, the PHC can be seen as having little resolution power.…”
Section: Discussionmentioning
confidence: 99%
“…10 The fact may be explained by the low expectations of people in relation to public health services, as a consequence of the access difficulty, because the simple fact of being attended can already produce satisfaction. 15 Another factor responsible for the high user satisfaction, especially public health services, is the bias of gratitude, which correlated with the reluctance to express negative opinions, both for fear of losing access to the service, and the dependency to professionals. 10 Considering the results, the research showed that users covered by the ESF in the municipality of Santa Cruz/RN are preponderantly women, white, married, Catholic, and belong to the age group of 18 to 30 years old.…”
Section: Satisfactionmentioning
confidence: 99%